Function-Based Design Principles for Additive Manufacturing - Filip Valjak; Dora Kosorčić; Marija Rešetar; Nenad Bojčetić (Applied Sciences, 2022)
The development of additive manufacturing (AM) technologies has brought new design possibilities, and to utilise those possibilities, new sources of AM design knowledge are needed. This paper presents an inductive methodology for extracting AM design knowledge based on the functional analysis of AM products. Extracted AM design knowledge is formalised in 32 AM design principles using the proposed methodology. The AM design principles are organised regarding the functions they solve. Initial validation and intended use are described through a case study. The AM design principles can facilitate systematic design processes and methods, and can be used in early design phases for finding partial solutions for subfunctions of the design problem.